Telomeres and Telomerase in The Aging Heart - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2017)
BACKGROUND: Aging per se is a risk factor for reduced cardiac function and heart diseases, even when adjusted for aging-associated cardiovascular risk factors. Accordingly, aging-related biochemical and cell-biological changes lead to pathophysiological conditions, especially reduced heart function and heart disease.CONTENT: Telomere dysfunction induces a profound p53-dependent repression of the master regulators of mitochondrial biogenesis and function, peroxisome proliferator-activated receptor gamma coactivator (PGC)-1a and PGC-1b in the heart, which leads to bioenergetic compromise due to impaired oxidative phosphorylation and ATP generation. This telomere-p53-PGC mitochondrial/metabolic axis integrates many factors linked to heart aging including increased DNA damage, p53 activation, mitochondrial, and metabolic dysfunction and provides a molecular basis of how dysfunctional telomeres can compromise cardiomyocytes and stem cell compartments in the heart to precipitate cardiac aging.SUMMARY: The aging myocardium with telomere shortening and accumulation of senescent cells restricts the tissue regenerative ability, which contributes to systolic or diastolic heart failure. Moreover, patients with ion-channel defects might have genetic imbalance caused by oxidative stress-related accelerated telomere shortening, which may subsequently cause sudden cardiac death. Telomere length can serve as a marker for the biological status of previous cell divisions and DNA damage with inflammation and oxidative stress. It can be integrated into current risk prediction and stratification models for cardiovascular diseases and can be used in precise personalized treatments.KEYWORDS: aging, telomere, telomerase, aging heart, mitochondria, cardiac stem cell